Assessment of different isotope dilution strategies and their combination with switchable solvent-based liquid phase microextraction prior to the quantification of bisphenol A at trace levels via GC-MS. (4th August 2020) - Bodur, Süleyman; Erarpat, Sezin; Chormey, Dotse Selali; Bozyiğit, Gamze Dalgıç; Öz, Ersoy; Özdoğan, Nizamettin; Bakırdere, Sezgin
Abstract : Different isotope dilution strategies were evaluated to quantify bisphenol A. High accuracy and precision were achieved by SS-LPME and ID 4 combination. Abstract : In this study, a novel analytical method was developed for the determination of trace level bisphenol A (BPA) in bottled water and wastewater samples. Switchable solvent-based liquid phase microextraction (SSLPME) was combined with quadrupole isotope dilution (ID 4 ) to improve the accuracy/precision and lower the detection limit. In the first step of this study, double isotope dilution (ID 2 ), triple isotope dilution (ID 3 ), quadrupole isotope dilution (ID 4 ), standard addition-double isotope dilution (SA-ID 2 ) and standard addition-triple isotope dilution (SA-ID 3 ) were applied for the determination of BPA to check their effectiveness in terms of accuracy and precision. ID 4 was selected as the best strategy to quantify the analyte. In order to improve the detection power, a microextraction strategy was adopted for the system and the developed combination called SSLPME-ID 4 -GC-MS was successfully applied for the trace quantification of BPA. Under the optimum conditions, percent recovery results were calculated as 99.4 ± 0.7% and 99.9 ± 0.8% for bottled water and wastewater samples spiked with BPA at 223.8 and 169.9 ng g −1, respectively.